ТРУДНОСТИ В ИЗУЧЕНИИ ИНОСТРАННОГО ЯЗЫКА И ПУТИ ПРЕОДОЛЕНИЯ ПРЕПЯТСТВИЙ НА ПУТИ К УСПЕХУ - Назарова Озода Шавкатовна (Journal Park Publishing, 2025)
The difficulties of language acquisition can lead to frustration, decreased motivation, and the temptation to give up. However, with the right strategies, mindset, and resources, these challenges can be overcome. This article explores the most common challenges associated with learning a foreign language, examines the psychological and cognitive factors that contribute to learner discouragement, and offers practical solutions achieve language-learning goals.
Keywords: Practical solutions, strategies, educators and learners, motivation, common challenges, language-learning.